Lifelong Physical Activity and Cardiovascular Autonomic Function in Midlife. Issue 8 (August 2016) - KIVINIEMI, ANTTI M.; PERKIÖMÄU, NELLI; AUVINEN, JUHA; HERRALA, SAULI; HAUTALA, ARTO J.; AHOLA, RIIKKA; TAMMELIN, TUIJA; TULPPO, MIKKO P.; JÄRVELIN, MARJO-RIITTA; KORPELAINEN, RAIJA; HUIKURI, HEIKKI V.
ABSTRACT: Purpose: Physical activity (PA) associates with cardiovascular autonomic function, but the relationship with lifelong PA is unclear. We hypothesized that lifelong PA would associate with cardiovascular autonomic function in midlife. Methods: At the age of 46 yr, the subjects of the prospective Northern Finland Birth Cohort 1966 were invited to examinations where vagally mediated heart rate variability (root mean square of the successive differences in RRi [rMSSD]) and cross-spectral baroreflex sensitivity (BRS) were analyzed from 3-min recordings of ECG and blood pressure in seated and standing positions. Three lifelong PA trajectory groups (active, semiactive, and inactive) were formed according to their self-reported frequencies of participation in PA at the ages of 14, 31, and 46 yr. Finally, 1283 men and 1779 women without cardiorespiratory diseases and diabetes had complete data on lifelong PA, covariates, and rMSSD, and 662 men and 807 women for BRS. Results: In both sexes and measurement conditions, the active ( P < 0.01) and semiactive groups ( P < 0.05) had greater rMSSD than the inactive group, and the highest BRS was observed in the active group (ANOVA P = 0.001–0.032). In men, these differences were not significant when adjusted for 46-yr lifestyle (smoking, alcohol consumption, sleep, and sitting time), body mass index, waist-to-hip ratio, blood pressure, lipid status, and glucose status. In women, lifelong PA remained a significant independent determinant of seated and standing rMSSD and standing BRS. Conclusion: Higher lifelong PA was associated with better cardiovascular autonomic function in midlife. In women, this effect was independent, but in men, it seemed to be mediated by the other lifestyle and cardiometabolic factors. Abstract : Supplemental digital content is available in the text.